Distribution of non-LEE-encoded type 3 secretion system dependent effectors in enteropathogenic Escherichia coli - Salvador, Fábia Andréia [UNIFESP] (2014)
Enteropathogenic Escherichia coli (EPEC) are important human gastroenteritis agents. The prevalence of six non-LEE genes encoding type 3 translocated effectors was investigated. The nleC, cif and nleB genes were more prevalent in typical than in atypical EPEC, although a higher diversity of genes combinations was observed in atypical EPEC.